Effect of ethanol-wet bonding on porosity and retention of fiberglass post to root dentin - Monize Ferreira Figueiredo de Carvalho; Monica Yamauti; Cláudia Silami de Magalhães; Aline Aredes Bicalho; Carlos José Soares; Allyson Nogueira Moreira
Abstract: This in vitro study aimed to assess the effects of different pretreatments used to adapt glass-fiber posts cemented to root canals with different resin cements, regarding porosity percentage and bond strength. Twelve bovine incisor roots were prepared with Largo drills. After post space preparation, the specimens were randomized into two types of pretreatment groups (n = 3): water-wet bonding and ethanol-wet bonding. After the post were cemented, the roots were stored in 100% humidity at room temperature for 7 days. The samples were scanned by microcomputed tomography (micro-CT). Images were reconstructed by NRecon software, and CTAn software was used to analyze the porosity percentage (%) at the luting interface. Evaluation of the push-out bond strength was performed by serially cutting the roots, and submitting the slices to testing. Additionally, the resin cement post-gel shrinkage values (%) were measured using the strain-gauge method (n = 10). Data were analyzed by two-way ANOVA, Tukey's test and Student's t test (a = 0.05). The roots prepared with ethanol-wet bonding using RelyX™ U200 had significantly lower porosity in the coronal and apical thirds (p < 0.05). The group prepared with ethanol-wet bonding using RelyX™ ARC presented better bond strength results in the coronal and apical thirds (p < 0.05). RelyX™ ARC (0.97%) produced a higher post-gel shrinkage value than RelyX™ U200 (0.77%). Canals pretreated with ethanol-wet bonding presented better outcomes in regard to porosity percentage and push-out bond strength.